2020
DOI: 10.3390/microorganisms8060796
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus cytotoxicus Isolated from a Pristine Natural Geothermal Area Reveals High Keratinolytic Activity

Abstract: Geothermal areas are the niches of a rich microbial diversity that is not only part of the intangible patrimony of a country but also the source of many microbial species with potential biotechnological applications. Particularly, microbial species in geothermal areas in Argentina have been scarcely explored regarding their possible biotechnological uses. The purpose of this work was to explore the proteolytic and keratinolytic enzymatic potential of microorganisms that inhabit in the Domuyo geothermal area in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…The ecological niche of B. cytotoxicus and the contamination pathway of potato products, however, remain unclear. Indeed, the first isolation of this species from a natural habitat (geothermal areas) was published only recently, but it does not provide any indication of potential food contamination pathways [ 15 ]. Stevens, et al [ 4 ] revealed that B. cytotoxicus harbors a putative hydroxyphenylalanine ( hpa ) operon, which is absent in the genomes of other B. cereus group members.…”
Section: Resultsmentioning
confidence: 99%
“…The ecological niche of B. cytotoxicus and the contamination pathway of potato products, however, remain unclear. Indeed, the first isolation of this species from a natural habitat (geothermal areas) was published only recently, but it does not provide any indication of potential food contamination pathways [ 15 ]. Stevens, et al [ 4 ] revealed that B. cytotoxicus harbors a putative hydroxyphenylalanine ( hpa ) operon, which is absent in the genomes of other B. cereus group members.…”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded that this putative evolutionary advantage might have been the reason for species differentiation [ 410 ]. Recently, Cavello et al first reported the isolation of B. cytotoxicus from the natural environment, a geothermal area, as well as its keratinolytic activity [ 411 ]. Interestingly, cytK-2 is not present in B. anthracis [ 125 ], but has been found in B. mycoides [ 412 ], very frequently in B. thuringiensis [ 125 , 210 ], and also outside the B. cereus group in Paenibacillus cookie [ 413 ].…”
Section: The Diarrheal Enterotoxinsmentioning
confidence: 99%
“…Although many keratinase producers have been isolated and identified ( Cavello et al, 2020 ; Jagadeesan et al, 2020 ; Moridshahi et al, 2020 ; Nnolim et al, 2020b ; Reis et al, 2020 ), the isolation and characterization of keratinase-producing microorganisms are still an important task. The keratin degradation efficiency can be improved when more keratinases are applied ( Peng et al, 2019 ).…”
Section: Mechanism Of Action For Keratinasementioning
confidence: 99%